Meta Analisis: Perbandingan Penggunaan Platform Pembelajaran Online dalam Meningkatkan Kemampuan Berpikir Peserta Didik - Rahman Daud, La Ode; Ridwan (Universitas Muslim Buton, 2023)
Online learning platforms are learning media used in distance learning activities. Online learning platforms are growing rapidly as a result of covid-19, currently many platforms are being used. Some of these platforms include Google meet, Zoom, Edmodo and WhatsApp. This research aims to compare several online learning platforms in improving students' critical thinking skills. The research uses a meta-analysis method, namely by searching for research that is relevant to the research topic on Google School. The research was then analyzed by calculating the effect size value. The results of the research show that the platforms that have the highest effect in improving students' critical thinking skills are Google meet, Edemo, Zoom and WhatsApp respectively with an effect size value of 0.50; 0.43; 0.39; and 0.23.